2012
DOI: 10.1080/08952833.2012.710815
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Skin Color on Heterosexual Black College Women's Dating Beliefs

Abstract: Black women’s skin color perceptions were identified utilized qualitative methods. The primary goal was to identify the relevance of these perceptions on their understandings about dating preferences and related beliefs about appropriate scripts using a Black feminist thought framework. Twenty- eight self- identified Black women attending a large university in the southeastern United States were interviewed for this study. Lighter- skin was perceived as being more attractive, and associated with four themes ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…For example, Golden (2004) details in her book, Don’t Play in the Sun , that her mother once told her not to play in the sun because “you’re going to have to get a light-skinned husband for the sake of your children as it is” (p. 4). As a result, these messages about skin-tone preference in the dating and mating markets also influence the dating attitudes and romantic experiences of African Americans (Hunter, 2013; Landor, 2017; Stephens & Thomas, 2012). Conversely, lighter skin is not always an advantage in the dating and mating market.…”
Section: Skin-tone Traumamentioning
confidence: 99%
“…For example, Golden (2004) details in her book, Don’t Play in the Sun , that her mother once told her not to play in the sun because “you’re going to have to get a light-skinned husband for the sake of your children as it is” (p. 4). As a result, these messages about skin-tone preference in the dating and mating markets also influence the dating attitudes and romantic experiences of African Americans (Hunter, 2013; Landor, 2017; Stephens & Thomas, 2012). Conversely, lighter skin is not always an advantage in the dating and mating market.…”
Section: Skin-tone Traumamentioning
confidence: 99%
“…Despite this lack of research, relevant studies that focus on African Americans and Latino/Latinas may offer some valuable insights concerning the causal mechanisms surrounding the relationship between skin tone and dating beliefs. For instance, several existing studies have used some variations of social perception theory to help shed light on this topic (Stephens & Fernandez, 2012; Stephens & Thomas, 2012). This framework posits that individuals form impressions of and make inferences about other people by drawing upon information from influential sources such as family members, friends, and the media (McArthur & Baron, 1983).…”
Section: The Impact Of Colorism On Dating Preferencesmentioning
confidence: 99%
“…Moreover, when creating the generalized “other,” individuals also develop impressions about themselves that may impact their own attitudes and behaviors (Jacobs, 2006). For example, in a study that investigated the influence of skin tone on dating beliefs among 28 African American college women, Stephens and Thomas (2012) found that most respondents viewed darker skinned women in a more negative light compared to their fairer skin counterparts. These women also believed that African American men ascribed similar undesirable characteristics (e.g., unattractive, loud, and unintelligent) to dark women.…”
Section: The Impact Of Colorism On Dating Preferencesmentioning
confidence: 99%
“…Most men in the study (74%) indicated they would prefer fair‐skinned women, 22% middle to the medium brown skin, and only 4% preferred a darker‐skin woman (Esmail & Sullivan, 2006). Other researchers confirm these findings of light skin preferences (e.g., Bodenhorn, 2006; Chaney & Perkins, 2018; Landor & Barr, 2018; Russell et al., 2013; Stephens & Thomas, 2012).…”
Section: Introductionmentioning
confidence: 73%